the THE EFFECT OF STAD TYPE COOPERATIVE LEARNING MODEL ON THE LEARNING OUTCOMES OF VIHARA DHAMMAPHALA SUNDAY SCHOOL- TANGERANG - Wina Dhamayanti; Dendang Sutikno (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2021)
This research was conducted based on the low value of the learning outcomes of Vihara Dhammapala Sunday school. The low learning outcomes are due to several factors, one of which is the ineffective learning model, therefore the existence of the Student Teams Achievement Divisions (STAD) learning model is one of the cooperative learning models in which there are several groups of students with different levels of academic ability. work together to realize learning objectives. This study aims to determine the effect of the STAD cooperative learning model on the learning outcomes of students at the Dhammaphala Vihara Sunday School. The design used in this research is in the form of an experiment with a quantitative approach. The instruments used in this study were questionnaires, documents and interviews. The questionnaire was distributed to 20 students. The data that has been obtained from the distribution of questionnaires were analyzed using the Likert scale and the learning outcomes of the pretest and posttest were analyzed using the paired t test. The results of this study indicate that the STAD learning model has a very strong effect on the learning outcomes of Buddhism, when viewed from the percent achievement of 91.75% then from the response evaluation answers with a total score of 1468 and a percent achievement of 91.81%. Furthermore, based on the paired t test the values before and after Dhammaphala Vihara Sunday School with a score of 14.82 turned out to be very significant with an average difference of 17.55. So, STAD learning model greatly enhances the value of learning outcomes at the Vihara Dhammaphala sunday school.